Neonatal Bacterial Meningitis: Single Reference Center Experience and Review of Current Literature: A Retrospective Cohort Study - Alper Aykanat; Hasan Tolga Celik; Gulsen Hazirolan; Sule Yigit; Murat Yurdakok (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Despite improvements in neonatal care, neonatal bacterial meningitis is still an emerging problem worldwide with high rates of mortality. The present study evaluates data on suspected- and culture-proven neonatal bacterial meningitis in the light of a single tertiary reference center experience in Turkey in comparison with the globe.